Solving with method of characteristics :
"f_x=-y, f_y=-x, f_z=0, f_p=q, f_q=p"
"\\dfrac{dx}{f_p}=\\dfrac{dy}{f_q}=\\dfrac{dz}{pf_p+qf_q}=\\dfrac{dp}{-(f_x+pf_z)}=\\dfrac{dq}{-(f_y+qf_z)}"
Solve
"\\dfrac{d^2p}{dt^2}=\\dfrac{dy}{dt}"
"\\dfrac{d^2p}{dt^2}=p"
"p=Ae^{t}+Be^{-t}"
"y=\\dfrac{dp}{dt}=Ae^{t}-Be^{-t}"
"x=\\dfrac{dq}{dt}=Ce^{t}-De^{-t}"
"\\dfrac{dz}{dt}=2pq=2(Ae^{t}+Be^{-t})(Ce^{t}+De^{-t})"
"=2ACe^{2t}+2BDe^{-2t}+2AD+2BC"
"z=ACe^{2t}-BDe^{-2t}+2ADt+2BCt+E"
"-(Ae^{t}-Be^{-t})(Ce^{t}-De^{-t})=0"
"=>AD+BC=0"
The initial data curve is written in parametric form as
Thus, using the initial data, the given PDE becomes
The strip condition gives
Therefore we have
Substitute
"A-B=0"
"AC-BD+E=s"
"A+B=1"
"C+D=0"
"A=\\dfrac{1}{2}, B=\\dfrac{1}{2}, C=\\dfrac{1}{2}s, D=-\\dfrac{1}{2}s, E=\\dfrac{1}{2}s"
Characteristics:
"y=\\dfrac{e^t-e^{-t}}{2}"
"z=\\dfrac{1}{2}(\\dfrac{e^{2t}+e^{-2t}}{2})s+\\dfrac{1}{2}"
"q=\\dfrac{e^t-e^{-t}}{2}s"
"x^2=s^2\\text{cosh}^2t , 1+y^2=1+\\text{sinh}^2t=\\text{cosh}^2t"
"z=\\dfrac{1}{2}s(\\text{cosh}(2t)+1)=s\\text{cosh}^2t"
"z^2=s^2\\text{cosh}^4t=x^2(1+y^2)"
Integral Surface:
Comments
Leave a comment